The Role of Viruses in Cellular Transformation and Cancer - Donath Damian (Cancer Reports)
ABSTRACT Background Viral infections are established contributors to oncogenesis, leading to significant public health challenges. This systematic review aims to synthesize current knowledge on the mechanisms of viral cellular transformation and their association with various cancers. Recent findings Studies reveal key mechanisms of oncogenesis, including direct viral integration into the host genome, expression of viral oncogenes, and indirect pathways such as chronic inflammation and immune evasion. Notably, Human Papillomavirus (HPV) was linked predominantly to cervical and oropharyngeal cancers, while Epstein–Barr Virus (EBV) was associated with lymphomas. Hepatitis B and C viruses were linked to liver cancer, highlighting the diverse impacts of viral infections on oncogenic processes. Conclusions This review underscores the complexity of viral interactions with host cells and their implications for cancer development. Findings suggest that targeted interventions, such as vaccination and antiviral therapies, may play a crucial role in reducing the incidence of virus‐related cancers. Further research is needed to explore novel therapeutic strategies and the role of co‐factors in viral oncogenesis.